Respectful and Non-abusive Care during Childbirth: an Urgent Need in Health Care Facilities - Gautam Bhattarai, Saraswoti Kumari (Journal of Nursing Education of Nepal, 2023)
Many women globally experience disrespectful, abusive or neglectful care/treatment during childbirth in facilities. Disrespectful and abusive care/treatment of women may occur throughout pregnancy, childbirth and the postpartum period, particularly vulnerable during childbirth. Such practices may have direct adverse consequences for both the mother and infant. Professional birth assistants and more humanized care are important vehicles for providing a safe and comforting birth experience for women. Fear of disrespect and abuse perpetuated by health workers, influence the women’s choice and decision to seek maternity care in the health facility. Key manifestations of disrespect and abuse include; physical abuse, non-consented care, non-confidential care, non-dignified care, discrimination, abandonment, and detention in facilities. Understanding the prevalence of disrespect and abuse is critical in developing interventions at national, health facility and community levels to address the factors and drivers that influence disrespect and abuse in facilities and to encourage clients’ future facility based maternity service utilization.
Keywords: NA